Outcomes of Dental Services Utilization of People in Kongkrailas District, Sukhothai Province - Suwonnoparat, Napa (Journal of Health Science of Thailand, 2020)
This study aimed to investigate results of the use of public dental service of people at Kongkrailas in Sukhothai in order to use the collected data to encourage people to use public dental services based on their medical rights. The secondary data was analyzed by HosXP of Kongkrailas hospital, using ICD-10 code on 1 October 2015 to 30 September 2018. It was found that an increase of people using services at Out-Patient Department at Kongkrailas hospital was similar. However, increases of people using dental services inside and outside Kongkrailas hospital were 13,861, 16,651 and 18,892 respectively. A majority of the dental service users was females, aged lower than 15 years old. They received services at hospitals in their hometowns, using their health insurance rights. In addition, some of the dental service users used the outside hospitals consisting of Ban Mai Sook Kasem Tambon Health Promoting Hospital, Prak Rak Tambon Health Promoting Hospital, Krai Nai Tambon Health Promoting Hospital and Nam Ruang Tambon Health Promoting Hospital. A majority of service users received dental examination, fillings and scaling. There is an increase of service users in dental services every year. Furthermore, when analyzing the service using rate of dental services in 100 people and the frequency of dental services in the use of dental services, dental examination, fillings and scaling every year. Public relations should apply cooperation with public health networks. The communities are important to help encourage people to recognize their own medical rights and dental service use and other health services based on their medical rights. This not only helps people to access appropriate medical services, but also enables people to have rapid transfer.